Simple change in logistic procedure improves response rate to QOL assessment: a report from the Japan Children's Cancer Group - Iori Sato; Takafumi Soejima; Yasushi Ishida; Miho Maeda; Katsuyoshi Koh; Kiyoko Kamibeppu (SpringerOpen, 2020)
Abstract Background Reducing non-completion of quality-of-life assessment in clinical trials is an important challenge in obtaining accurate data and unbiased interpretation of patients' quality-of-life for each regimen. We evaluated the effect of changing our questionnaire distribution procedure in a multicenter phase II/III trial on the response rate to a quality-of-life questionnaire. Methods In the trial, we distributed 1767 questionnaires and 1045 were returned. We adopted a regression discontinuing design and estimated the change in response rate between pre-intervention (quality-of-life questionnaires were sent to each center soon after patient registration) and post-intervention (a set of tailored questionnaires was sent just before the first quality-of-life assessment). Results The post-intervention response rate was higher (odds ratio = 1.62) than the pre-intervention response rate. Conclusions A simple logistic intervention reduced the non-completion of QOL assessment in this case, suggesting that a simple change can contribute to improving clinical trial accomplishment.